RADT-36. MANAGEMENT OF PATIENTS WITH METASTATIC CENTRAL NERVOUS SYSTEM (CNS) GERMINOMA; A LITERATURE REVIEW. (14th November 2022) - Abu-Arja, Mohammad; Shatara, Margaret; Okcu, M Fatih; McGovern, Susan; Su, Jack M; Abdelbaki, Mohamed
Abstract: BACKGROUND: No consensus exists on the optimal irradiation volume/dose for patients with metastatic CNS germinoma. We reviewed the literature for a potential association between different treatment modalities and survival. METHODS: We searched PubMed for studies on patients with primary metastatic CNS germinoma including detailed survival outcome data. We used the Kaplan-Meier method to estimate event-free survival (EFS) rates and log-rank test for comparison among treatment modalities. RESULTS: We identified 124 patients from 38 studies published between 1990 and 2021. The median age of presentation was 15 years (range: 1.5–47 years). Treatment modalities included: chemotherapy only (n = 5), radiotherapy only (n = 31), and radio-chemotherapy (n = 88). Radiotherapy modalities included: craniospinal irradiation (CSI) (n = 69), whole-brain irradiation (WBI) (n = 19), whole ventricular irradiation (WVI) (n=16), focal and spine irradiation (n = 5), focal irradiation only (n = 9), and not specified (n = 1). The median focal irradiation dose was 36.6 Gy (range:19.5-59.8 Gy). The median doses for CSI, WBI, and WVI were 24 Gy (range: 10.8-49 Gy). Eighteen patients relapsed, 111 were alive without disease, 2 were alive with disease, and 12 died of disease. The median follow-up time was 5 years in survivors. Four patients who received only chemotherapy relapsed. Five-year EFS rates were similar in patients who received chemo-radiotherapy and radiotherapy alone (89%, 95%CI 81-97%, vs 88%, 95%CI 74-100%, p = 0.6). Patients who were treated with CSI had a longer 5-year EFS compared to patients treated with other modalities (92%, 95%CI 84-100% vs 80%, 95%CI 64-94% p = 0.03). EFS was similar in patients treated with CSI whether they received ≥ 24 Gy or less. CONCLUSION: CSI is required to achieve prolonged relapse-free survival (RFS). CSI dose of < 24 Gy may be sufficient to achieve sustained RFS. Future trials are needed to evaluate the potential role of neoadjuvant chemotherapy in reducing the dose/volume of irradiation in patients with metastatic CNS germinoma.